Some Biological activities of ethanol extract of Marrubium globosum - Mustafa Pehlivan; Falah Saleh Mohammed; Ali Erdem Şabik; Eylem Kına; Muhittin Dogan; Önder Yumrutaş; Mustafa Sevindik (Turkish Journal of Agriculture: Food Science and Technology)
Plants have been used for centuries to treat various diseases. In this study, Marrubium globosum Montbret & Aucher ex Benth. plant was used as a material. The extract of the plant was extracted with the help of soxhlet device using ethanol, which is a good polar solvent, and Rel Assay kits were used to determine the oxidant and antioxidant levels in the plant extract. Antifungal and antibacterial activities of M. globossum were tested against standard bacteria and fungus strains by agar dilution method. As a result of the analysis, TAS value of plant extract was determined as 7.677±0.231, TOS value as 12.387±0.083 and OSI value as 0.162±0.004. In this context, it has been observed that the plant has an important antioxidant potential. In addition, the plant extract was found to be effective against test microorganisms at 50-200 μg/mL extract concentrations. As a result, it has been determined that M. globossum can be a natural antioxidant and antimicrobial source.